Opinions and interest in Science and Technology in Ecuadorian teenagers - Camacho , M. Alejandra (2022)
This work aimed to explore the interests and opinions about science and technology and the influence of gender on Ecuadorian students. For this, the Relevance of Scientific Education (ROSE) questionnaire was applied to a sample of 1,054 students between 16 and 18 years of age in the second and third years of the Unified General Baccalaureate (BGU). The results show favorable opinions towards science and technology, but only moderate interest in adolescents, who, in general, prefer not to receive more classes in these subjects. On the other hand, students are positive about the impact science and technology have on society. Finally, variations were found in the distribution of the topics of interest according to gender. The implications of these results, the current situation of the Ecuadorian science curriculum, and future research are discussed.